ASSA14-03-23 CREG over-expression in BMSC protect against myocardial infarction via VHL/HIF-1α/VEGF pathway mediated vascularisation. (1st December 2014) - Peng, CF; Tian, XX; Deng, J; Wang, J; Yan, CH; Yang-Li,; Tao, J; Han, YL
Abstract : Background: We hypothesised that mesenchymal stem cells (MSCs) overexpressing Cellular Repressor of E1A-stimulated Genes (CREG) showed improved survival and engraftment in the infarcted heart and promoted vascularisation through paracrine release of vascular endothelial growth factor (VEGF) and activation of the HIF-1α signal pathway. Methods: Mononuclear cells derived from rat bone marrow were isolated by density-gradient centrifugation and were cultured on fibronectin-coated plates, supplied with bovine pituitary extract. After the marrow-derived mesenchymal stem cells over-expressed CREG, we compare with the production of VEGF by ELISA and the protein expression of HIF-1α in different groups by western blot under hypoxia. Rat bone marrow–derived MSCs were used as nontransduced ( Norm MSCs) or transduced with adenoviral-GFP vector ( GFP MSCs) or vector encoding for GFP-CREG ( CREG MSCs). Results: For in vivo studies, 50 μl of DMEM without cells (group 1) or containing 1.5×10 6Norm MSCs (group 2) or GFP MSCs (group 3) or CREG MSCs (group 4) were implanted intramyocardially in rat model of permanent coronary artery occlusion. one week later, immunoblot on rat heart tissue (n = 4 per group) showed highest survival of CREG MSCs (p < 0.06 vs Norm MSCs and GFP MSCs)(n = 6 per group). Confocal imaging after immunostaining for CD31 showed extensive angiomyogenesis in the infarcted heart. Infarction size was significantly reduced in cell transplanted groups compared with the control. Indices of left ventricular function, including ejection fraction and fractional shortening, were improved in group 4 as compared with group 1 (p < 0.05). In vitro, under hypoxia the secretion of VEGF are most in the supernatant from the MSCs over-expression CREG. And the supernatants from BMSC over-expressed CREG exhibited a significant increase in angiogenic tube formation. In addition, the expression of CREG begins to appear after hypoxia. Molecular studies revealed that under hypoxia CREG active HIF-1α, but not HIF-2α, HIF-1β and we use the inhibition of HIF-1α confirm it. Further, we found that CREG can not influence the HIF-1α mRNA synthesis but it can inhibit the expression of pVHL which is the key protein regulation degradation of HIF-1α. Conclusions: The strategies of CREG transgene expression inhibit pVHL and induced HIF-1α signalling and culminated in extensive angiomyogenesis in the infarcted heart.